The effect of performing mental exertion during cycling endurance exercise on fatigue indices: sex dependent differences - Amoozi, H.; Barzegarpoor, H.; Rajabi, H.; Button, D.C.; Fayazmilani, R. (Frontiers in Physiology, 2025)
Introduction: Men and women have different performance abilities, where women have greater tolerance for fatigue in long-distance exercise. Part of this greater tolerance may be due, in part, differences in men`s and women`s mental fatigue capacity during exercise. Thus, the aim of this study was to examine the effect of cycling endurance exercise, along with mental fatigue, on the sex dependent differences in exercise tolerance.